Basal Temperature, Cervical Mucous, and Both Combination as Diagnostic Tools to Detect Ovulation: Akurasi Suhu Basal Tubuh, Lendir Serviks, dan Kombinasi Keduanya sebagai Alat Pendeteksi Ovulasi - Eka R Gunardi; Alexander Mukti; Â Herbert Situmorang (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To make basal body temperature examination andcervical mucus as an alternative examination in detectingovulation, especially in health facilities that do not have ultrasound. Methods: This cross-sectional study was conducted at the outpatientclinic of RSUPN Dr. Cipto Mangunkusumo in the year2016-2017. A total of 49 infertile female patients who had normalmenstrual cycles were asked to participate and performedbasal body temperature measurements, cervical mucussampling and transvaginal ultrasound examination, the dataare subsequently grouped into 3 Days Estimated Ovulation(DEO); DEO-2 days, DEO and DEO+ 2 days. Diagnostic testswere performed and accurate comparison between basal bodytemperature, cervical mucus and a combination of both werelater assessed. Results: The best accuracy was found on cervical mucus andcombination of both with 65% in detecting ovulation, whilstthe lowest was basal body temperature (59%) with sensitivity46.7%, and specificity 78.9%. Cervical mucus in diagnosingovulation has a sensitivity of 70% and specificity 57.8%. Thecombination of temperature-cervical mucus in diagnosing ovulationhas sensitivity of 46.67% and specificity of 94.73%. Conclusion: Cervical mucus examination has better accuracy comparedwith basal body temperature examination in detecting ovulation.Further research for validating these diagnostic tools to thewider community and not only in patients with infertility is needed. Keywords: basal body temperature, cervical mucus, infertility, ovulationdetection, ultrasound